Assessing the Quality of Supervision Experiences in the Different Research Stages at Postgraduate Level - Tooba Saleem; Nasir Mehmood (Journal of Education and Educational Development, 2020)
The nature of supervisory relationship is dynamic that changes over the course of candidacy. Subsequently, the supervision demands of supervisees also change to help them in performing certain tasks at specific research stages. In this context, this research is proposed to investigate the supervision experiences of supervisees in four different research stages (i.e. Stage 1: developing synopsis, Stage 2: collecting data, Stage 3: writing thesis and Stage 4: submitted thesis). In the light of six supervision aspects (i.e. Project management, Intellectual support, pertinent research skills, Inter-personal communication skills, Workload management and Supportive skills) the quality of supervision was assessed from supervisees’ perspective. Cross-sectional survey design was used to assess the supervision experiences of (N=422) supervisees in four distinct stages of research supervision. The data were collected from 12 public and private universities of the Punjab. For this study, a multi-sectioned, self-constructed Supervisor-Supervisee Relationship Questionnaire (Saleem, 2014) was used. The findings of the study highlighted the need to train the supervisors to manage their time not just in terms of teaching and supervision of research students, but also keeping the stages of their research in mind. By addressing the stage specific needs of supervisees the quality of supervision could be improved.
Keywords: Supervision Experiences; Research Stages; Supervisor-Supervisee Relationship; Supervision dynamics; Quality of supervision